2009
DOI: 10.1158/1535-7163.mct-09-0106
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant CPE fused to tumor necrosis factor targets human ovarian cancer cells expressing the claudin-3 and claudin-4 receptors

Abstract: Using gene expression profiling, others and we have recently found that claudin-3 (CLDN3) and claudin-4 (CLDN4) are two of the most highly and consistently upregulated genes in ovarian carcinomas. Because these tight junction proteins are the naturally occurring receptors for Clostridium perfringens enterotoxin (CPE), in this study, we used the COOH-terminal 30 amino acids of the CPE (CPE 290-319 ), a fragment that is known to retain full binding affinity but have no cytolytic effect, to target tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…Here, particularly the claudin-specific binding property of the CPE C-terminal domain was employed to target other toxins, such as diphteria toxin fragment A (DT-A), Pseudomonas aeroginosa exotoxin (PE) or TNF-a. [39][40][41][42][43] These approaches exploit CPE-mediated targeting to introduce the toxic proteins into tumor cells, and were shown to be effective in vitro and in vivo. These strategies aimed rather at improvement of cytotoxicities of DT-A, PE or TNF-a, than the toxicity of CPE itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, particularly the claudin-specific binding property of the CPE C-terminal domain was employed to target other toxins, such as diphteria toxin fragment A (DT-A), Pseudomonas aeroginosa exotoxin (PE) or TNF-a. [39][40][41][42][43] These approaches exploit CPE-mediated targeting to introduce the toxic proteins into tumor cells, and were shown to be effective in vitro and in vivo. These strategies aimed rather at improvement of cytotoxicities of DT-A, PE or TNF-a, than the toxicity of CPE itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo frequent applications of CPE and of CPE-fusion proteins were required to achieve therapeutic effects. [39][40][41]43 In contrast, CPE as a sole full-length protein combines both strong target specificity and very efficient cytotoxicity, which is important for in vivo applications to achieve rapid tumor destruction. This study demonstrated that although CPE is produced inside the transfected cells, its outside action for pore formation and cell lysis is not hampered.…”
Section: Discussionmentioning
confidence: 99%
“…The human ovarian carcinoma cell line 2008 was grown in RPMI 1640 supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin, and 100 mg/ml streptomycin. Its two sublines 2008-CLDN3KD-4.5 and 2008-CLDN4KD-5.5, identified here as CLDN3KD and CLDN4KD in which CLDN3 or CLDN4 has been knocked down (Yuan et al, 2009), were cultured in the RPMI 1640 medium supplemented with 10% FBS, antibiotics, and 10 mg/ml puromycin. We used pcDNA-hCTR1, a pcDNA3.1 vector containing full-length human CTR1 cDNA and expressing a Geneticin (G418) resistance marker (Moller et al, 2000), to transfect 2008, CLDN3KD, and CLDN4KD cells using Lipofectamine (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…What role these proteins serve in ovarian cancers is largely unknown, and data from studies addressing this question have yielded conflicting results (reviewed in Hewitt et al, 2006;Kominsky, 2006;Ouban and Ahmed, 2010). CLDN3 and CLDN4 are of particular interest in ovarian cancer therapy because CLDN3 and CLDN4 are the only transmembrane tissue-specific claudins capable of mediating Clostridium perfringens enterotoxin binding and cytolysis (Katahira et al, 1997); therefore, they have attracted attention as potential therapeutic targets (Morin, 2005;Kominsky, 2006;Kominsky et al, 2007;Yuan et al, 2009;Saeki et al, 2010). We made the novel observation that CLDN3 and CLDN4 modulate sensitivity to the cytotoxic effect of cDDP.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate and ovarian cancer cell lines expressing claudins 3 and 4 clostridium perfringens enterotoxin is able to destroy such cells (75,76). Claudins 3 and 4 are, however, expressed in many non-neoplastic cells so CPE cannot be used in treatment of cancer without side effects even though the cytotoxicity appears to be lower in nonneoplastic cells (76).…”
Section: Claudins In Diagnosis and Treatment Of Germ Cell Tumorsmentioning
confidence: 99%